Assessment of venous blood collection practices among medical laboratory workers in Edo State, Nigeria - Oladeinde, Bankole Henry; Omoregie, Richard; Ekejindu, Ifeoma Mercy (Journal of Laboratory and Precision Medicine, 2017)
Background: Phlebotomy is a complex process requiring knowledge and skill to perform safely. This study aimed at identifying deviations from best phlebotomy practices among laboratory workers involved in venous blood draws in Edo State, Nigeria. Methods: A total of 109 participants from public and private laboratories in Edo State, Nigeria were assessed as they performed venous draws on patients. Results: All participants identified patients by their full names only, and did not introduce themselves to patients before initiating venous draws. Only 9 (8.2%) participants obtained patients consent before venous draws. Glove use was significantly associated with participants [medical laboratory scientists: odd ratio (OR), 14.850; 95% confidence interval (CI): 3.345, 65.916; P